Communication and information sharing with pediatric patients including refugees with advanced cancer, their caregivers, and health care professionals in Jordan: a qualitative study - Alarjeh, Ghadeer; Boufkhed, Sabah; Alrjoub, Waleed; Guo, Ping; Yurduşen, Sema; Ahmed, Fahad; Abdal-Rahman, Mousa; Alajarmeh, Sawsan; Alnassan, Anwar; Al-Awady, Shireen; Kutluk, Tezer; Harding, Richard; et al. (Frontiers in Oncology, 2023)
Introduction Effective communication in pediatric palliative cancer care is an important aspect of practice to enhance patient- and family-centered care, and to optimize decision-making. However, little is known about communication preferences practices from the perspectives of children, caregivers and their health care professionals (HCPs) in the Middle Eastern region. Furthermore, involving children in research is crucial but limited. This study aimed to describe the communication and information-sharing preferences and practices of children with advanced cancer, their caregivers, and health care professionals in Jordan. Methods A qualitative cross-sectional study was conducted using semi-structured face to face interviews with three groups of stakeholders (children, caregivers and HCPs). Purposive sampling recruited a diverse sample from inpatient and outpatient settings at a tertiary cancer center in Jordan. Procedures were in line with the Consolidated criteria for reporting qualitative research (COREQ) reporting guidelines. Verbatim transcripts were thematically analyzed. Findings Fifty-two stakeholders participated: 43 Jordanian and 9 refugees (25 children, 15 caregivers and 12 HCPs). Four major themes emerged: 1) Hiding information between the three stakeholders which includes parents who hide the information from their sick children and ask the HCPs to do so to protect the child from distressful emotions and children who hide their suffering from their parents to protect them from being sad; 2) Communication and sharing of clinical versus non-clinical information; 3) Preferred communication styles such as use of a companionate approach by acknowledging patients and caregivers’ suffering, building a trustful relationship, proactive information sharing, considering child age and medical status, parents as facilitators in communication, and patients’ and caregivers’ health literacy; 4) Communication and information sharing with refugees where they had dialect issues, which hindered effective communication. Some refugees had unrealistically high expectations regarding their child’s care and prognosis, which posed challenges to communication with staff. Discussion The novel findings of this study should inform better child-centered practices and better engage them in their care decisions. This study has demonstrated children’s ability to engage in primary research and to express preferences, and parents’ ability to share views on this sensitive topic.